2017
DOI: 10.1186/s40659-017-0117-8
|View full text |Cite
|
Sign up to set email alerts
|

Proton NMR characterization of intact primary and metastatic melanoma cells in 2D & 3D cultures

Abstract: ObjectiveTo characterize the differences between the primary and metastatic melanoma cell lines grown in 2D cultures and 3D cultures.MethodsPrimary melanoma cells (WM115) and metastatic melanoma cells (WM266) extracted from a single donor was cultured in 2D as well as 3D cultures. These cells were characterized using proton NMR spectrometry, and the qualitative chemical shifts markers were identified and discussed.ResultsIn monolayer culture (2D), we observed one qualitative chemical shift marker for primary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…Thereby, the remarkably increased levels of hypoxanthine are tightly linked to the significantly decreased contents of inosine in the WM2664 metastatic melanoma cells (FC NMR = 0.49; FC MS = 0.48). It seems that primary melanoma favors the metabolic route of inosine monophosphate to guanosine (FC MS = 0.42), a molecule that is notably elevated in the WM115 cells and has been suggested to serve as biomarker [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereby, the remarkably increased levels of hypoxanthine are tightly linked to the significantly decreased contents of inosine in the WM2664 metastatic melanoma cells (FC NMR = 0.49; FC MS = 0.48). It seems that primary melanoma favors the metabolic route of inosine monophosphate to guanosine (FC MS = 0.42), a molecule that is notably elevated in the WM115 cells and has been suggested to serve as biomarker [14].…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma cells have also been examined by employing NMR analysis, which underlined the enhanced glutaminolysis and oxidative phosphorylation, as well as the deregulated choline and lipid metabolism [12,13]. WM115 and WM2664 cell metabolisms have been studied using intact cells, or after extraction, showing that glucose accumulation and phospholipid composition differ significantly between the two cell types [14,15].In the present study, the cell lines WM115 (primary tumor) and WM2664 (lymph-node metastases) that have derived from the same patient, and thus carry comparable and metastasis-related mutational signatures, were thoroughly examined, conducting an untargeted NMR-and UHPLC-HRMS-mediated metabolomics analysis, in order to obtain a better understanding of the underlying biochemistry characterizing these cancer-cell, metastasis-dependent, types. Besides the novel information produced, combination of these two analytical methodologies provides the unambiguous verification of metabolites [7] being essentially engaged in advanced melanoma metastasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To understand how metabolism is rewired in melanoma, previous metabolomics studies using various analytical techniques focused on the identification of metabolic profiles in melanoma tissue samples, biofluids or cell lines. Increased amino acids, especially glutamine and glutamate, and decreased glucose levels have been associated with melanoma metastasis [ 29 , 30 , 41 , 42 , 43 , 44 , 45 , 46 ]. Metabolites related to protein methylation correlated with metastatic capacity of human melanoma xenografts [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro-grown spheroids also show similar changes in their metabolism, indicating that this model system is a suitable mimetic of in vivo tumors. Moreover, metabolic biomarkers can now be readily used to identify tumors (Ramachandran et al 2016 ; Ramachandran and Yeow 2017 ). Finally, Duer et al have elegantly already demonstrated the potential of multidimensional ssNMR in cell tissue preparations and revealed 2D ssNMR correlations in murine ECM and tissue-culture derived ECM samples (Chow et al 2014 ; Wong et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%